Activated Carbon from Sawdust Biomass Via ZnCl₂ and NaOH Activation for Water Biofiltration Applications - Syarwan Hamid; Gusnawati; Thahirah Arief; Muh. Ilham Anggamulia; Hijrah Amaliah Azis; Muh Arman (Candela Edutech Indonesia, 2025)
The declining availability of fossil energy sources in Indonesia has driven the development of renewable and environmentally friendly alternatives, including the utilization of biomass waste such as teak sawdust (Tectona grandis L.F.). This study aims to produce activated carbon via pyrolysis and chemical activation using ZnCl₂ and NaOH for water filtration applications. Pyrolysis was conducted at 300-400°C with biomass-to-activator ratios of 1:3, 1:5, and 1:7. SEM analysis revealed that chemical activation increased pore number and size; ZnCl₂ produced larger and more complex pore structures, while NaOH resulted in more uniform pores. FTIR spectra showed a reduction in hydroxyl (O–H), carbonyl (C=O), and ether (C–O) groups with increasing temperature, along with the emergence of aromatic (C=C) bands, indicating enhanced carbonization and structural stability. NaOH activation at 380°C yielded the highest iodine adsorption (1124 mg/g), while ZnCl₂ was optimal at 320 °C (980 mg/g). These results demonstrate that teak sawdust-derived activated carbon possesses a microporous structure and functional surface groups suitable for water purification and efficient removal of organic contaminants